Image encryption using anti-synchronisation and Bogdanov transformation map. (9th April 2022) - Al-Hazaimeh, Obaida M.; Al-Jamal, Mohammad F.; Alomari, A.K.; Bawaneh, Mohammed J.; Tahat, Nedal
A new image encryption algorithm based on anti-synchronisation of Chen system and Bogdanov map is presented in this paper. To illustrate the performance and robustness of the new algorithm, some of security analyses against different cryptanalytic attacks are presented. The security analyses found that, the new algorithm can be applied to provide a suitable application through insecure networks (i.e., internet). As well as, the anti-synchronisation Chen system and Bogdanov transformation map not just limited to digital image encryption, but can be applied directly in several other applications such as real-time application (i.e., video encryption).